THE ROLE OF SCENARIO PLANNING IN DEVELOPING STRATEGIC LEADERSHIP AMONG MANAGERS OF COMMERCIAL COMPANIES IN BAGHDAD - Assistant Teacher: Kazem Mahmoud Abdul Qader; Assistant Teacher: Areej Faeq Abdel (Scholars Digest Publishing, 2023)
The current research aims to identifyThe role of scenario planning in developing strategic leadership among managers of commercial companies in BaghdadWhere the importance of the current research is highlighted in thatScenario planning is an effective way to develop the company's strategic leadership. It allows the company to know the opportunities and risks it faces in the market, and helps to make well-planned and elaborate decisions.While the research problem lies inThe use of scenario planning in the development of strategic leadership by defining the company's goal and related objectives, and this helps in determining the required directions and strategic plans that will be implemented to achieve the company's goal and identifying the expected opportunities and risks and the specific factors that affect the company, and this helps in determining the required possibilities and lines of action To deal with expected opportunities and risks.
Keywords: scenario planning, strategic leadership, company managers, development.